Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3904/kjim.2020.120
|View full text |Cite
|
Sign up to set email alerts
|

Current status of heart failure: global and Korea

Abstract: Heart failure (HF) is a condition in which the heart is unable to pump enough blood to meet the body's needs for blood and oxygen. Thus, HF is a grave disease with high morbidity and mortality. Because the prevalence of and exposure to the risk factors for HF increase with age, the prevalence of HF has been increasing in an aging society, including Korea. The vast advancement of medical and device therapy has improved the outcomes of HF, but significant residual risk still exists, and the benefit is confined t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 60 publications
(72 reference statements)
1
37
0
Order By: Relevance
“…4 It was estimated that the prevalence of heart failure worldwide was between 0.1% and 6.7%. 5 The determination of peripheral leukocytes, mainly neutrophils, and counting was a cheap and widely available method to assess the presence of any inflammation. Studies had shown that patients with heart failure had higher circulating levels of pro-inflammatory cytokines, including non-cellular and cellular components, compared with healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…4 It was estimated that the prevalence of heart failure worldwide was between 0.1% and 6.7%. 5 The determination of peripheral leukocytes, mainly neutrophils, and counting was a cheap and widely available method to assess the presence of any inflammation. Studies had shown that patients with heart failure had higher circulating levels of pro-inflammatory cytokines, including non-cellular and cellular components, compared with healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…Not all diabetic patients develop HF, and not all HF patients have diabetes [ 7 , 8 ]. Nonetheless, diabetes is an important risk factor for the development of HF.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study of pooled data from European, American, and Asian populations with HF (with reduced ejection fraction) showed that the rate of cardiovascular death/hospitalization for HF is higher in Asia than in Western Europe and North America [12]. This has also been shown in Korean HF registries [13].…”
Section: Introductionmentioning
confidence: 90%